PENGARUH DIGITALISASI SISTEM TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI PADA KANTOR DESA PEDUNGAN - Anak Agung Istri Agung Ovy Dwijayanthi; Kadek Intan Rusmayanthi; Tjokorda Gde Agung Wijaya Kesuma Suryawan (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2026)
With organizational commitment serving as a moderator, this research seeks to examine the impact of system digitization on staff performance at the Pedungan Village Office. One kind of governance modernization that has the potential to boost productivity and morale in the workplace is the digitization of administrative and attendance-related parts of the system. All thirty-five workers were surveyed for this quantitative investigation, which employed a saturated sample method. In order to assess the direct and indirect relationships between variables, data was gathered using a Likert-scale questionnaire and analyzed using the Partial Least Squares (PLS) technique. According to the findings, digitization of systems significantly improves worker productivity. Organizational commitment is also greatly enhanced by digitalizing systems. The connection between digitization of systems and performance is moderated by organizational commitment, which has a substantial impact on employee performance. That is to say, in order to increase performance, the level of organizational commitment grows in direct proportion to the degree to which systems are digitalized. In addition to improving technical efficiency, this discovery shows that digital transformation in the workplace greatly contributes to a healthy work culture by making employees more invested in the company's success. Findings from this research have important practical implications, such as the need to enhance staff performance in the village government setting via the development and implementation of digital technologies.